Exploration of candidate genes derived from SNPs associated with phenotypic root plasticity using Philippine rice germplasm for drought adaptation - Agustin, Nonawin Lucob; Cruz, Antoinette S.; Lipio, Patrick Louie G.; Cabral, Maria Corazon J.; Mananghaya, Teodora E.; Suralta, Roel R.; Niones, Jonathan M. (Vol. 150, No. 6B (December 2021) pages 1647-1662.)
Phenotypic root plasticity is a crucial trait for stable growth, adaptability, and productivity under abiotic-stressed growing environments. However, the genetic determinants and mechanisms controlling the trait are largely unknown, thus limiting its breeding application. We previously found 17 single nucleotide polymorphism (SNPs) significantly associated with phenotypic root plasticity traits - particularly, total root length (TRL), total nodal root length (TNRL), and total lateral root length (TLRL) - under moderate and severe drought using selected Philippine rice germplasm by employing the genome-wide association studies (GWAS) approach. - Title page.